Character matters : and other life lessons from George H. W. Bush - Becker, Jean, approximately 1956- (Twelve, 2024)
"As America heads into what promises to be a tumultuous 2024 presidential election year, Character Matters will be a good reminder of the importance of character when defining true leadership. Colleagues, friends, and family will share their often very personal stories of what they learned from watching and listening to President Bush, including former United States Secretary of State Condoleezza Rice; Secretary of State James A. Baker; stand-up comedian Dana Carvey; "Queen of Country" star Reba McEntire; American columnist for The New York Times Maureen Dowd; American novelist Brad Meltzer; presidential biographer Jon Meacham; former Prime Minister of the United Kingdom John Major; former Prime Minister of Canada Brian Mulroney; Secretary of Defense Robert Gates; the Oak Ridge Boys and best-selling author Christopher Buckley; and of course his grandchildren. Character Matters will illustrate how George Bush never stopped showing us the way to lead by example"--